High-strength creep-resistant recyclable diene-based elastomer and method for preparing same

CN116874697BActive Publication Date: 2026-11-03SICHUAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310963886.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2026-11-03
Estimated Expiration
2043-08-02

AI Technical Summary

Technical Problem

The recycling of existing rubber products is difficult to achieve sustainability and high-strength creep resistance. Dynamic covalent crosslinked elastomers are difficult to control exchange kinetics at high molecular weights, which affects the processing and performance of the materials.

Method used

By combining dynamic covalent bonds and phase separation structures, isoprene-styrene block copolymers are prepared to form vinyl urethane networks. The phase separation structure and crosslinking density are then controlled to enhance the creep resistance and recyclability of the materials.

Benefits of technology

This invention achieves a high-strength, creep-resistant recyclable rubber material with shape memory and self-healing properties, improving the material's mechanical properties and thermal stability, and enhancing recycling efficiency and reprocessing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116874697B_ABST
    Figure CN116874697B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of high-strength creep-resistant recyclable diene elastomer and its preparation method, belong to high polymer field.The present application provides a kind of high-strength creep-resistant recyclable diene elastomer as follows: first, the block polymer of styrene or its derivative and isoprene and hydroxyl lauricene is prepared, then the obtained block polymer is sequentially treated by acetylation and crosslinking treatment, and the diene elastomer of vinyl carbamate bond crosslinking is prepared.The present application combines glassy polymer dynamic chemistry crosslinking system with physical crosslinking system, i.e.combining dynamic covalent bond with phase separation structure, can reduce the creep at room temperature, while realizing the enhancement of comprehensive performance such as mechanical property, recycling performance etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-strength, creep-resistant, recyclable diene elastomer and its preparation method, belonging to the field of polymers. Background Technology

[0002] Covalent crosslinking of rubber is crucial for achieving excellent elasticity, mechanical properties, dimensional stability, and solvent resistance; however, it also presents challenges to the recycling of rubber products. The increasing production and consumption of rubber products have led to significant environmental pollution and the depletion of fossil fuels. In recent years, considerable efforts have been made to process waste rubber, such as mechanical grinding to produce abrasive tire powder, pyrolysis for oil recovery, and desulfurization to recycle rubber. However, these methods are either energy-intensive or environmentally unfriendly, limiting exports to very specific and relatively marginal applications. Therefore, initiating a truly sustainable recycling cycle remains a significant challenge. Designing and introducing dynamic networks to make rubber recyclable and even repairable is a recycling strategy that addresses the issue at its source.

[0003] Currently, there are two main methods for "preventing rubber waste." The first is to introduce non-covalent bonds, i.e., physical cross-linking (such as phase separation or crystallization, hydrogen bonding, ionic bonding, and supramolecular interactions like fillers). These bonds can reversibly break and recombine under external stimuli. However, due to the relatively weak bond energy, these elastomers have low mechanical strength and poor heat and solvent resistance. The second method involves dynamic covalent cross-linking, such as dissociative covalent cross-linking or associative covalent cross-linking (vitrimer (glass-like polymers)). This method combines excellent recyclability and mechanical properties, and generally possesses excellent thermal stability and solvent resistance, offering hope for solving the recycling problem of cured rubber.

[0004] Dynamically covalently crosslinked elastomers, especially vitrimers (glass-like polymers), combine the reprocessability of thermoplastics with the excellent mechanical properties of thermosetting materials. Their reprocessability stems from the ability of the dynamic covalently crosslinked network to undergo bond exchange at high temperatures. It is known that the bond exchange reaction of epoxy esters, commonly used in rubber recycling, is slow, requiring high catalyst loading and high temperatures to occur within a reasonable timeframe. However, some vitrimers exhibit relatively rapid exchange reactions at room temperature. This low-temperature exchange reaction produces interesting self-healing properties, but it also has limitations at low glass transition temperatures (T0). gVitrimer materials exhibit unwanted deformation at their service temperatures. Therefore, vitrimer is a very challenging material, requiring precise control of its exchange kinetics to achieve rapid processing at high temperatures (high exchange rate) and good dimensional stability at service temperatures (no creep or very low exchange rate). Furthermore, the relaxation behavior of dynamically covalently crosslinked elastomers is highly dependent on the material's molecular weight and crosslinking density; as the molecular weight increases, the material's recyclability is affected. Although much research has been conducted on the shortcomings of vitrimer and corresponding progress has been made, this generally requires precise control of exchange kinetics. When vitrimer is applied to high-molecular-weight elastomers, expecting them to exhibit the same rapid processing and dimensional stability, the network migration limitations imposed by the high molecular weight make it difficult to achieve the same precise control of exchange kinetics. Summary of the Invention

[0005] To address the aforementioned shortcomings, this invention combines the Vitrimer dynamic chemical crosslinking system with a physical crosslinking system, that is, combining dynamic covalent bonds with a phase-separated structure. This reduces creep at room temperature while simultaneously enhancing overall performance, including mechanical properties and recyclability. Specifically, a high molecular weight isoprene-styrene block copolymer was first prepared and a vinyl urethane network was formed. The effect of the phase-separated structure on the material's mechanical properties and dimensional stability was studied by changing the polystyrene phase content. Then, the relaxation behavior and recyclability of the high molecular weight polymer network were further controlled by changing the crosslinking density.

[0006] The first technical problem to be solved by this invention is to provide a high-strength, creep-resistant, recyclable diene elastomer having the following structure:

[0007]

[0008] Furthermore, a, b, m, and n are each integers greater than 1. Generally speaking, the ranges of a, b, m, and n are unrestricted. For example, a, b, m, and n can each be integers within the ranges of 1-10, 1-20, 1-50, 1-100, 1-200, 1-500, 1-1000, 1-2000, 1-5000, 1-10000, etc. For example, the numerical ranges of a, b, m, and n can be selected from 0-114, 10-28, 1200-1386, etc.

[0009] Further, R is selected from hydrogen, halogen, or alkyl. Even further, halogen can include chlorine. Even further, alkyl can include methyl, ethyl, propyl, tert-butyl, etc.

[0010] Furthermore, the high-strength, creep-resistant, recyclable diene elastomer is prepared as follows: first, a block polymer of styrene or its derivatives with isoprene and hydroxymyrcene is obtained; then, the obtained block polymer is subjected to acetylation and crosslinking treatments in sequence to obtain a diene elastomer crosslinked with vinyl urethane bonds.

[0011] Furthermore, the mass fraction of styrene segments in the high-strength, creep-resistant, recyclable diene elastomer is 5-13%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, and any range and value between the aforementioned values, preferably 6-12.5%, more preferably 6.2-12.17%, even more preferably 9-10%, and most preferably 9.21-9.77%.

[0012] Further, the mass fraction of hydroxymyrcene segments in the high-strength, creep-resistant, recyclable diene elastomer is 2-7%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, and any range and value between the foregoing values, preferably 2.5-6.9%, more preferably 2.59-6.8%, more preferably 4.6-4.8%, and most preferably 4.66-4.74%. Further, the crosslinking ratio of the high-strength, creep-resistant, recyclable diene elastomer is 3 × 10⁻⁶. -5 mol / cm 3 -14×10 -5 mol / cm 3 3.4×10 is preferred. -5 mol / cm 3 -13×10 -5 mol / cm 3 More preferably 3.47×10 -5 mol / cm 3 -12.93×10 -5 mol / cm 3 More preferably 7.2×10 -5 mol / cm 3 -7.7×10 -5 mol / cm 3 The optimal value is 7.25×10. -5 mol / cm 3 -7.69×10 -5 mol / cm 3 .

[0013] Furthermore, the cis content of the isoprene-hydroxymyrcene copolymer segments in the high-strength, creep-resistant, recyclable diene elastomer reaches over 96%.

[0014] The second technical problem to be solved by the present invention is to provide a method for preparing a high-strength, creep-resistant, recyclable diene elastomer. The preparation method is as follows: first, a block polymer of styrene or its derivatives with isoprene and hydroxymyrcene is prepared, and then the obtained block polymer is subjected to acetylation treatment and cross-linking treatment in sequence to obtain a diene elastomer cross-linked with vinyl urethane bonds.

[0015] More specifically, the method includes the following steps:

[0016] (1) Preparation of block polymers of styrene or its derivatives with isoprene and hydroxymyrcene: styrene or its derivative monomers dissolved in organic solvent I are polymerized for a period of time in the presence of catalyst I. Then, a mixed solution of hydroxymyrcene aluminum oxychloride monomer and isoprene monomer is added for copolymerization. The reaction is then quenched. The resulting products are washed with acidified water and ethanol, and dried to obtain the block polymer.

[0017] (2) Preparation of acetylated styrene or its derivatives into block polymers with isoprene and hydroxymyrcene: Under a protective atmosphere, the block polymer obtained in step (1) is dissolved in organic solvent II, and then acylated with diketene in the presence of catalyst II. Vacuum distillation is performed to remove at least part (e.g., most or all) of organic solvent II. The resulting product is precipitated in a solvent, washed, and dried to obtain the acetylated block polymer.

[0018] (3) Preparation of a block polymer of styrene or its derivatives crosslinked with vinyl urethane bonds and isoprene and hydroxymyrcene: The acetylated block polymer obtained in step (2) is dissolved in organic solvent III, and then a diamine crosslinking agent and catalyst III are added to carry out a crosslinking reaction to obtain a block polymer of styrene or its derivatives crosslinked with vinyl urethane bonds and isoprene and hydroxymyrcene, which is the high-strength creep-resistant recyclable diene elastomer.

[0019] Furthermore, the organic solvent I in step (1) includes cyclohexane, n-hexane or n-heptane, preferably cyclohexane.

[0020] Further, catalyst I in step (1) is a mixture of substances A, B, C and D, wherein the molar ratio of substances A, B, C and D is: A:B:C:D = 0.8-1.2:10-20:15-25:0.08-0.12, preferably, A:B:C:D = 1:15:20:0.1; substance A is neodymium carboxylic acid neodymium, neodymium alcohol neodymium, neodymium phosphate ester neodymium, neodymium acetylacetone neodymium or amino neodymium; substance B is triisobutylaluminum or trioctylnediium. The following substances are used: trimethylaluminum, triethylaluminum, or diisobutylaluminum hydride; substance C is chloroform, diisobutylaluminum chloride, dichlorodimethylsilane, tert-butyl chloride, tetrachloromethane, diethylaluminum chloride, aluminum trichloride, diethylaluminum chloride, or trichlorotriethylaluminum; substance D is ethyl trichloroacetate, butyl trichloroacetate, isoamyl trichloroacetate, or ethyl trichlorobutyrate; preferably, substance A is neodymium neodecanoate; substance B is triisobutylaluminum; substance C is chloroform; and substance D is ethyl trichloroacetate.

[0021] Further, in step (1), the first part of the styrene or its derivative monomer is first aged with substances A and B in the catalyst I at 40-60°C for 5-20 min, then substances C and D are added, and the reaction continues for 0.5-2 h, then the second part of the styrene or its derivative monomer is added, and polymerization is carried out at 40-60°C for 5-20 h. The molar ratio of the first part to the second part of the styrene or its derivative monomer is 1:20-50, for example, 1:20, 1:21, 1:22, 1:23, 1:24, 1:25, 1:26, 1:27, 1:28, 1:29, 1:30, 1:31, 1:32, 1:33, 1:34, 1:35, 1:36, 1:37, 1:38, 1:39, 1:40, 1:41, 1:42, 1:43, 1:44, 1:45, 1:46, 1:47, 1:48, 1:49, 1:50. Preferably, the molar ratio of the first part to the second part of the styrene or its derivative monomer is 1:40.

[0022] Furthermore, in step (1), the cis content of isoprene and hydroxymyrcene copolymer segments in the block polymer of styrene or its derivatives prepared using catalyst I is above 96%.

[0023] Further, in step (1), the molar ratio of styrene or its derivative monomer (the sum of the first part and the second part) to substance A in catalyst I is 420-1020:0.8-1.2, preferably 820:1.

[0024] Further, in step (1), the molar ratio of styrene or its derivative monomer, isoprene monomer, and hydroxymyrcene aluminum oxychloride monomer is 160-400:400-470:5-21. Preferably, in step (1), the molar ratio of styrene or its derivative monomer, isoprene monomer, and hydroxymyrcene aluminum oxychloride monomer is 163.8-397.8:410-468:5.85-20.5. Preferably, in step (1), the molar ratio of styrene or its derivative monomer, isoprene monomer, and hydroxymyrcene aluminum oxychloride monomer is 319.8:429:12.8.

[0025] Further, the hydroxymyrcene aluminum oxychloride monomer is prepared as follows: the independent double bonds of myrcene are epoxidized with m-chloroperoxybenzoic acid to obtain epoxidized myrcene; lithium aluminum hydride is used to perform an epoxidation-reduction reaction with epoxidized myrcene to obtain hydroxymyrcene; and alkyl aluminum is used to perform a hydroxy dehydrogenation reaction with hydroxymyrcene to obtain the hydroxymyrcene aluminum oxychloride monomer.

[0026] Further, the alkyl aluminum is selected from triisobutylaluminum, triethylaluminum, diisobutylaluminum hydride, trimethylaluminum, triethylaluminum, tri-n-propylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tripentylaluminum, trihexylaluminum, or trioctylaluminum. Preferably, the alkyl aluminum is selected from diisobutylaluminum hydride.

[0027] Furthermore, in step (1), the copolymerization is carried out at 40-60°C for 5-20 hours.

[0028] Furthermore, in step (1), the quenching reaction is carried out using ethanol.

[0029] Furthermore, in step (2), the protective atmosphere can be a nitrogen or argon protective atmosphere.

[0030] Further, in step (2), the organic solvent II comprises tetrahydrofuran (THF) or toluene, with tetrahydrofuran being the most preferred.

[0031] Further, in step (2), catalyst II can be any suitable catalyst that promotes the hydroxylation reaction. Examples of such catalysts may include 4-dimethylaminopyridine. Preferably, catalyst II is 4-dimethylaminopyridine.

[0032] Further, in step (2), catalyst II is added to the block polymer solution under ice bath and stirring conditions, and then divinyl ketone is slowly added dropwise.

[0033] Further, in step (2), the acylation reaction is carried out at 0°C for 0.5-1.5 h, and then at room temperature for 3-5 h.

[0034] Further, in step (2), the resulting product is precipitated in ethanol and washed with ethanol.

[0035] Further, in step (3), the organic solvent III comprises anhydrous toluene or anhydrous tetrahydrofuran, preferably anhydrous toluene.

[0036] Furthermore, in step (3), the diamine crosslinking agent comprises any suitable diamine small molecule. Examples of such diamine crosslinking agents may include 4,7,10-trioxo-1,13-tetanediamine.

[0037] Furthermore, in step (3), catalyst III comprises any suitable Brønsted acid catalyst. Examples of such catalysts may include p-toluenesulfonic acid.

[0038] Further, in step (3), a diamine crosslinker with a content of 1:1 molar equivalent relative to the acetylated styrene or its derivative in the block polymer of isoprene and hydroxymyrcene and a catalyst III with a content of 0.5:1 molar equivalent are added.

[0039] Furthermore, the mass fraction of styrene segments in the high-strength, creep-resistant, recyclable diene elastomer prepared by the method described above is 5-13%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, and any range and value between the aforementioned values, preferably 6-12.5%, more preferably 6.2-12.17%, more preferably 9-10%, and most preferably 9.21-9.77%.

[0040] Furthermore, the mass fraction of hydroxymyrcene segments in the high-strength, creep-resistant, recyclable diene elastomer prepared by the method described above is 2-7%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, and any range and value between the foregoing values, preferably 2.5-6.9%, more preferably 2.59-6.8%, more preferably 4.6-4.8%, and most preferably 4.66-4.74%.

[0041] Furthermore, the crosslinking ratio of the high-strength, creep-resistant, recyclable diene elastomer prepared by the method described above is 3 × 10⁻⁶. -5 mol / cm 3 -14×10 -5 mol / cm 3 3.4×10 is preferred. -5 mol / cm 3 -13×10 -5 mol / cm3 More preferably 3.47×10 -5 mol / cm 3 -12.93×10 -5 mol / cm 3 More preferably 7.2×10 -5 mol / cm 3 -7.7×10 -5 mol / cm 3 The optimal value is 7.25×10. -5 mol / cm 3 -7.69×10 -5 mol / cm 3 .

[0042] In other respects, the present invention also provides a catalyst system for preparing high cis polyisoprene, said catalyst system being a mixture of substances A, B, C and D, wherein the molar ratio of substances A, B, C and D is: A:B:C:D = 0.8-1.2:10-20:15-25:0.08-0.12, preferably, A:B:C:D = 1:15:20:0.1.

[0043] Furthermore, substance A is neodymium in carboxylic acids, neodymium in alcohols, neodymium in phosphate esters, neodymium in acetylacetones, or neodymium in amino groups; substance B is triisobutylaluminum, trioctylnedioxide, trimethylaluminum, triethylaluminum, or diisobutylaluminum hydride; substance C is chloroform, diisobutylaluminum chloride, dichlorodimethylsilane, tert-butyl chloride, tetrachloromethane, diethylaluminum chloride, aluminum trichloride, diethylaluminum chloride, or trichlorotriethylaluminum; and substance D is ethyl trichloroacetate, butyl trichloroacetate, isoamyl trichloroacetate, or ethyl trichlorobutyrate.

[0044] Preferably, substance A is neodymium neodecanoate; substance B is triisobutylaluminum; substance C is chloroform; and substance D is ethyl trichloroacetate.

[0045] Furthermore, the polyisoprene prepared using the catalyst system has a cis content of over 96%.

[0046] In other respects, the present invention also provides the use of the catalyst system described above for the preparation of high-cis polyisoprene. The polyisoprene prepared using the catalyst system has a cis content of 96% or higher.

[0047] The beneficial effects of this invention are:

[0048] (1) This invention successfully prepared diene elastomers with different styrene contents and different crosslinking ratios; through GPC and 1¹H NMR confirmed that all samples had similar molecular weights and molecular weight distributions, ensuring a single variable. FTIR, swelling experiments, DSC, AFM, and DMA demonstrated the successful preparation of covalently cross-linked elastomers with microphase separation structures. Adjustable plastic phase ratios and cross-linking densities were successfully achieved through simple polymer sequence manipulation.

[0049] (2) The exchange of vinyl urethane bonds and the dissociation of polystyrene phase endow the dynamic covalent crosslinked elastomer with some intelligent responses, including shape memory and self-healing properties, laying the foundation for the practical application of the material.

[0050] (3) The phase separation structure of plastics can significantly improve the creep resistance of materials at the operating temperature, while the increase in the crosslinking ratio can significantly improve the recyclability of materials. In addition, these two factors also have a certain promoting effect on other properties such as mechanical properties and thermal stability. This provides a new approach for preparing high-strength, creep-resistant, and recyclable diene elastomers. Attached Figure Description

[0051] Figure 1 The 1H NMR spectrum of the epoxy myrcene (EMY) prepared in Example 1 is shown.

[0052] Figure 2 The 1H NMR spectrum of hydroxymyrcene (HMY) prepared in Example 1 is shown.

[0053] Figure 3 The synthetic route of the hydroxymyrcene aluminum oxychloride monomer is shown.

[0054] Figure 4 The 1H NMR spectrum of PS3IM2-OH prepared in Example 1 is shown.

[0055] Figure 5 The 1H NMR spectrum of PS2IM2-OH prepared in Example 1 is shown.

[0056] Figure 6 The 1H NMR spectrum of PS1IM2-OH prepared in Example 1 is shown.

[0057] Figure 7 The 1H NMR spectrum of PSOIM2-OH prepared in Example 1 is shown.

[0058] Figure 8 The hydrogen NMR spectrum of the PS3IM2-AC prepared in Example 1 is shown.

[0059] Figure 9 The 1H NMR spectrum of the PS2IM2-AC prepared in Example 1 is shown.

[0060] Figure 10The 1H NMR spectrum of the PS1IM2-AC prepared in Example 1 is shown.

[0061] Figure 11 The hydrogen NMR spectrum of the PSOIM2-AC prepared in Example 1 is shown.

[0062] Figure 12 The PS shown in Example 1 is displayed. x IM y Synthesis route diagram of -VU(x=0,1,2,3;y=2).

[0063] Figure 13 The 1H NMR spectrum of PS2IM3-OH prepared in Example 2 is shown.

[0064] Figure 14 The 1H NMR spectrum of PS2IM1-OH prepared in Example 2 is shown.

[0065] Figure 15 The 1H NMR spectrum of the PS2IM3-AC prepared in Example 2 is shown.

[0066] Figure 16 The 1H NMR spectrum of the PS2IM1-AC prepared in Example 2 is shown.

[0067] Figure 17 The PS prepared in Example 1 is shown. x Crosslinking density, gel fraction, and swelling ratio of IM2-VU.

[0068] Figure 18 The PS prepared in Example 1 is shown. x Infrared spectrum of IM2.

[0069] Figure 19 The PS2IM prepared in Example 2 is shown. y -VU crosslinking density, gel fraction, and swelling ratio.

[0070] Figure 20 The PS2IM prepared in Example 2 is shown. y The infrared spectrum.

[0071] Figure 21 The PS2IM prepared in Example 2 is shown. y Infrared stretching vibration peak spectrum of the NH group.

[0072] Figure 22 The stress-strain curves of the specimens prepared in Examples 1 and 2 are shown.

[0073] Figure 23The creep-recovery test results of the samples prepared in Examples 1 and 2 are shown in the figure.

[0074] Figure 24 The stress relaxation test results of the specimens prepared in Examples 1 and 2 are shown in the figure.

[0075] Figure 25 The recovery performance of the samples prepared in Examples 1 and 2 is shown.

[0076] Figure 26 The comparison of the strength and elongation at break of the PS2IM2-VU sample prepared in Example 1 with the recycling performance of other dynamically covalently crosslinked diene elastomers (such as cis-butadiene rubber PB, styrene-butadiene rubber SBR, natural rubber NR, isoprene rubber IR, etc.) is shown.

[0077] Figure 27 The self-healing properties of the PS2IM2-VU sample prepared in Example 1 are shown.

[0078] Figure 28 The PS2IM2-OH prepared in Example 1 and the PS prepared in Example 3 are shown. 1 The glass transition temperature of 2IM2-OH. Detailed Implementation

[0079] This paper describes the preparation of a polymer with styrene blocks and isoprene and hydroxymyrcene random copolymer blocks by coordination polymerization. Subsequently, the hydroxymyrcene blocks were acetylated and the polymer was crosslinked using a diamine crosslinking agent to finally obtain a polystyrene-based dynamically covalently crosslinked elastomer with a vinyl urethane network.

[0080] This invention prepares a high-strength, creep-resistant, recyclable diene elastomer by constructing a dynamic covalent cross-linked network and a phase separation structure. Introducing a polystyrene phase enables microphase separation, thereby achieving enhanced macroscopic deformation resistance at room temperature. On the other hand, the cross-linking density significantly affects the relaxation behavior of the dynamic cross-linked network. Therefore, by controlling the cross-linking density, the relaxation behavior and recyclability of the material at high temperatures can be further optimized, while simultaneously adjusting the material's creep resistance. By adjusting the introduced microphase separation structure and the cross-linking density, the overall properties of the material can be controlled, potentially leading to the preparation of a high-strength, creep-resistant, recyclable diene elastomer.

[0081] The swelling experiment, TGA, DSC, and FTIR confirmed the PS content of the sample. 1-3IM2-VU (S, I, and M represent styrene, isoprene, and hydroxymyrcene, respectively, and VU represents vinyl urethane) exhibits a consistent chemical crosslinking ratio, phase-separated structure, and a small number of hydrogen bonds. DMA temperature scanning curves demonstrated that the obtained material possesses excellent low-temperature resistance and thermal stability that increases with increasing styrene content. Tensile testing investigated the mechanical properties of the samples; the number of physical crosslinking points increased with increasing styrene content, thus improving the material's mechanical strength. On the other hand, AFM testing showed that the polystyrene phase of PS2IM2-VU with moderate styrene content was uniformly distributed in a spherical pattern within the diene matrix, forming a well-separated two-phase structure, resulting in the best mechanical properties. WAXD and SAXS tests also indicated that with increasing styrene content, the samples exhibited higher orientation and better strain-induced crystallization behavior, thereby improving the material's modulus and tensile properties. Tensile cycling and permanent deformation measurements showed that dynamic covalent crosslinking imparted good elasticity to the samples. Creep experiments showed that increasing styrene content significantly improved the material's resistance to macroscopic deformation at operating temperatures (<90℃). Stress relaxation and recovery experiments showed that the introduction of styrene significantly increased the relaxation rate of the samples and decreased the exchange activation energy and topological freezing transition temperature (T0). v This improves the recovery efficiency of mechanical properties.

[0082] The TGA, DSC, and DMA temperature scans confirmed that the sample possesses a good phase separation structure, excellent low-temperature resistance, and thermal stability. FTIR analysis revealed a small number of hydrogen bonds in the sample. The polystyrene phase introduces physical crosslinking points, enhancing the material's resistance to macroscopic deformation, i.e., creep resistance, at conventional operating temperatures. For example, at 60°C, the creep and permanent deformation of PS3IM2-VU with the highest styrene content were 7.2% and 1.2%, respectively, while those of PS0IM2-VU without styrene were 11.0% and 2.1%, respectively. Furthermore, the material's thermal stability, mechanical properties, and relaxation properties were all improved. Increasing the styrene content promotes the orientation of the large-scale structure, thereby enhancing strain-induced crystallization behavior and improving the material's mechanical properties. With the increase of polystyrene phase content, the modulus of the material increased from 1.6 MPa to 3.2 MPa, while the elongation at break did not decrease significantly. Among them, PS2IM2-VU, which has a better phase separation structure, has the best mechanical strength (15.7 MPa) and toughness (41.0 MJ / m). 3 The strengths of PS and styrene-free random copolymers are 2.21 times and 2.75 times that of PS0IM2-VU, respectively. Compared to styrene-free random copolymers, the melt dissociation of the PS phase at high temperatures can accelerate the relaxation rate of the material, reduce the activation energy, and achieve excellent reprocessing performance and recycling efficiency (strength recovery rate of over 65% and toughness recovery rate of over 70%).

[0083] The styrene content of PS2IM2-VU, which exhibits the best overall performance, was kept constant to investigate the effect of chemical crosslinking density on material properties. Test results show that increasing crosslinking density significantly improves the material's elasticity, dimensional stability, and mechanical properties. PS2IM3-VU with the highest crosslinking ratio still maintains 22% creep and 10% permanent deformation at 180℃. Increasing the crosslinking ratio promotes material orientation and crystallization, enhancing mechanical properties. However, when the crosslinking ratio reaches its maximum, the excessively high proportion of relatively permanent crosslinks and entanglements leads to a severe decrease in elongation at break, resulting in a deterioration in mechanical strength. Furthermore, the material's relaxation and recovery properties are also improved to some extent. Due to the effects of free amines, catalysts, and hydrogen bonds, the relaxation rate increases with increasing crosslinking ratio, the bond exchange activation energy decreases from 32.72 kJ / mol to 25.29 kJ / mol, and the recovery rate of mechanical properties after recovery also increases. Specifically, PS2IM3-VU with the highest crosslinking ratio achieves a tensile strength recovery rate of 89% and a toughness recovery rate of 95.4%. In addition, the material also possesses some functional properties, such as shape memory and self-healing properties, and the presence of the polystyrene phase is particularly important in these two aspects.

[0084] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.

[0085] For the block polymerization of conjugated dienes and styrene, this invention employs a rare-earth catalytic system with active properties: neodymium neodecanoate / triisobutylaluminum / trichloromethane / ethyl trichloroacetate (Nd(VA)3 / Al(i-Bu)3 / CHCl3 / Cl3CCO2CH2CH3). First, styrene monomer is polymerized. After a period of polymerization, a mixed solution of hydroxymyrcene aluminum oxide monomer (HMY-Al) and isoprene monomer (IP) is added for copolymerization, thereby preparing a copolymer with two blocks of styrene and diene. By changing the feed rate and polymerization time, the ratio and length of the two blocks can be controlled to obtain polymers (PS) with different polystyrene block ratios. x IM y -OH, x=1,2,3,y=2, S, I and M represent styrene, isoprene and hydroxymyrcene, respectively, and x and y represent the content of styrene repeating units and hydroxymyrcene repeating units, respectively. In addition, the same catalytic system was used to carry out random copolymerization of hydroxymyrcene aluminum oxychloride monomer and isoprene monomer to prepare a styrene-free control polymer PS0IM2-OH.

[0086] Example 1

[0087] Preparation of hydroxymyrcene aluminum oxychloride monomer (HMY-Al)

[0088] 1) Preparation of myrcene oxide (EMY)

[0089] Myrcene (MY, 54.5 g, 400 mmol) was dissolved in 300 mL of dichloromethane and placed in an ice-water bath. m-chlorobenzoic acid peroxide (m-CPBA, 71.1 g, 300 mmol) was slowly added in portions to the myrcene solution. The reaction was carried out at 0 °C for 1 h, followed by 4 h at room temperature. After the reaction was complete, the mixture was filtered. The filtrate was washed with sodium hydroxide solution, and the organic phase was collected separately. The organic phase was washed with water until neutral, then dried over saturated sodium chloride solution and anhydrous magnesium sulfate. After standing for 12 h, the mixture was filtered and evaporated to dryness to obtain crude myrcene oxide (a pale yellow oily liquid). The crude product was purified by silica gel column chromatography (eluent: petroleum ether: ethyl acetate = 100:1) to obtain a colorless oily liquid (yield 40–60%). The 1H NMR spectrum is attached. Figure 1 As shown.

[0090] 2) Preparation of hydroxymyrcene (HMY)

[0091] All operations were performed under argon protection. Purified EMY (10 g, 65.8 mmol) was placed in a reaction flask, cooled in an ice-water bath at 0°C, and 110 mL of dehydrated THF was added. After bubbling with argon for 20 min, lithium aluminum hydride solution (5 g, 131.6 mmol) was added dropwise using a syringe, and the mixture was stirred overnight. After the reaction was complete, the reaction apparatus was placed in an ice-water bath, and water was slowly added dropwise until all excess lithium aluminum hydride was removed. Then, 10% hydrochloric acid solution was added until the white precipitate formed in the previous step dissolved. The reaction mixture was extracted and separated using dichloromethane. The organic phase was washed with water until neutral, then dried over saturated sodium chloride solution and anhydrous magnesium sulfate. After standing for 12 h, the mixture was filtered and evaporated to dryness to obtain crude hydroxymyrcene. The crude product was separated and purified by silica gel column chromatography (eluent: petroleum ether: ethyl acetate = 50:1) to obtain a colorless oily liquid (yield >80%). The 1H NMR spectrum is attached. Figure 2 As shown.

[0092] 3) Preparation of hydroxymyrcene aluminum oxychloride monomer (HMY-Al)

[0093] All operations were performed under argon protection. HMY was dissolved in anhydrous n-hexane (4.32 g, 28 mmol, 2 M), bubbled with argon for 30 min, and then the reaction flask was placed in a liquid nitrogen-ethyl acetate cooling bath. Diisobutylaluminum hydride (28 mL, 28 mmol, 1 M) was slowly added dropwise, and the reaction was carried out at low temperature for 12 h to obtain hydroxymyrcene aluminum oxychloride (HMY-Al), with the structure shown in Formula I. After the reaction, the reaction solution was transferred to a glove box and filtered. The solid content was calculated to be 60 mg / mL, and then the solution was stored in a sealed refrigerator. The synthetic route of the hydroxymyrcene aluminum oxychloride monomer is attached. Figure 3 As shown.

[0094] 4) Polymer PS x IM y Preparation of (x = 0, 1, 2, 3; y = 2)

[0095] A)PS x IM y Preparation of -OH (x = 0, 1, 2, 3; y = 2)

[0096] PS x IM y The preparation of -OH (x=1,2,3; y=2) is as follows: Nd(VA)3 (1.82mL, 0.39mmol, 141mg / mL), styrene (0.78M cyclohexane solution, 7.8mmol, 9.897mL), and Al(i-Bu)3 (5.85mL, 5.85mmol) are added to a reaction flask and aged at 50℃ for 10min. Then, CHCl3 (632uL, 7.8mmol) and ethyl trichloroacetate (0.073M cyclohexane solution, 0.039mmol, 5.42mL) are added to the reaction flask and reacted for 1h before use. Then, styrene (5.78M cyclohexane solution, 27mL, 156mmol, x=1; 54mL, 312mmol, x=2; 67.5mL, 390mmol, x=3) was added, and polymerization was carried out at 50℃ for 12h. Then, a mixed solution of isoprene (41mL, 410mmol, x=1; 42.9mL, 429mmol, x=2; 46.8mL, 468mmol, x=3) and HMY-Al (62.7mL, 12.8mmol, 60mg / mL) was added, and the reaction was continued at 50℃ for 12h. Ethanol was then added to quench the reaction. The polymer was washed with acidified water and ethanol, respectively, and then dried in a vacuum oven at 40°C for three days to obtain a white polymer. The yields of the polymer were determined (20.1 g, 72.0%, x = 1; 18 g, 61.4%, x = 2; 16.8 g, 52.7%, x = 3, based on the yield of polyisoprene). The 1H NMR spectrum is attached. Figure 4 , 5 As shown in Figure 6.

[0097] B)PS x IM y The preparation of -OH (x=0; y=2) was as follows: Nd(VA)3 (1.82 mL, 0.39 mmol, 141 mg / mL), isoprene (0.5 M cyclohexane solution, 0.78 mL, 7.8 mmol), and Al(i-Bu)3 (5.85 mL, 5.85 mmol) were added to a reaction flask and aged at 50 °C for 10 min. Then, CHCl3 (632 μL, 7.8 mmol) and ethyl trichloroacetate (0.073 M cyclohexane solution, 0.039 mmol, 5.42 mL) were added to the reaction flask, and the reaction was allowed to proceed for 1 h. A mixed solution of isoprene (46.8 mL, 468 mmol) and HMY-Al (45.9 mL, 9.36 mmol, 60 mg / mL) was then added, and the reaction was continued at 50 °C for 12 h. The reaction was then quenched with ethanol. The polymer was washed with acidified water and ethanol, respectively, and then dried in a vacuum oven at 40°C for three days to obtain a white polymer (25 g, 78.4%). The 1H NMR spectrum is attached. Figure 7 As shown. All aggregation operations are performed in the glove box.

[0098] The polymer prepared by the rare earth catalytic system used in this invention can have a cis content of over 96%, making it a high-cis polyisoprene.

[0099] 5) PS x IM y Preparation of -AC(x=0,1,2,3;y=2)

[0100] Under an argon atmosphere, polymer PS x IM y -OH (5 g) was dissolved in 300 mL of THF in a round-bottom flask. After dissolution, the flask was placed in an ice-water bath, and DMAP (2.53 g, 0.069 M) was added with stirring. Then, diketene (1.67 mL, 0.069 M) was slowly added dropwise. After the addition was complete, the reaction was carried out at 0 °C for 1 h, and then at room temperature for 4 h. Most of the solvent was removed by vacuum distillation, and then the product was precipitated in a large amount of ethanol. The crude product was washed three times with ethanol and dried under vacuum at 40 °C for three days until constant weight was obtained. The resulting pale yellow polymer was named PS. x IM y -AC, where AC represents acetylacetyl. The 1H NMR spectrum is attached. Figure 8 , 9 As shown in Figures 10 and 11.

[0101] 6) PS x IM y Preparation of -VU(x=0,1,2,3;y=2)

[0102] Taking PS2IM2-AC as an example, PS2IM2-AC (5 g, 0.99 mmol acetoacetyl) was dissolved in anhydrous toluene, and then 4,7,10-trioxo-1,13-tetanediamine (217 μL, 0.99 mmol) and p-toluenesulfonic acid (34.1 mg, 1.98 mmol, 50 mg / mL in THF) were added. The mixture was stirred at room temperature for 30 min, poured into glass petri dishes, and placed in a vacuum oven at 40 °C for 2 days, followed by 1 day at 80 °C. The resulting pale yellow film was named PS2IM2-VU, where VU represents vinyl carbamate. Other proportions of PS x IM y The preparation method of -VU is as described above.

[0103] PS x IM y The synthesis route of -VU(x=0,1,2,3;y=2) is attached. Figure 12 As shown.

[0104] Example 2

[0105] 1) Preparation of hydroxymyrcene aluminum oxychloride monomer (HMY-Al): Same as in Example 1.

[0106] 2) Polymer PS x IM y Preparation of (x = 2; y = 1, 3): All polymerization operations were performed in a glove box.

[0107] Nd(VA)3 (1.82 mL, 0.39 mmol, 141 mg / mL), styrene (0.78 M cyclohexane solution, 7.8 mmol, 9.897 mL), and Al(i-Bu)3 (5.85 mL, 5.85 mmol) were added to the reaction flask and aged at 50 °C for 10 min. Then, CHCl3 (632 μL, 7.8 mmol) and ethyl trichloroacetate (0.073 M cyclohexane solution, 0.039 mmol, 5.42 mL) were added to the reaction flask and reacted for 1 h before use. Styrene (54 mL, 312 mmol) was added, and polymerization was carried out at 50 °C for 12 h. Then, a mixed solution of isoprene (42.9 mL, 429 mmol, y = 2) and HMY-Al (28.7 mL, 5.85 mmol, y = 1; 100.4 mL, 20.5 mmol, y = 3; 60 mg / mL) was added, and the reaction was continued at 50 °C for another 12 h. Ethanol was then added to quench the reaction. The polymer was washed with acidified water and ethanol, respectively, and then dried in a vacuum oven at 40 °C for three days to obtain a white polymer. The yield of the polymer was determined (19.5 g, 66.6%, y = 1; 17.3 g, 59.0%, y = 3, based on the yield of polyisoprene). The 1H NMR spectrum is attached. Figure 13 , 14 As shown, the cis content of the copolymer segment of polyisoprene and hydroxymyrcene is over 96%, making it a high-cis polyisoprene.

[0108] 3) PS x IM y Preparation of -AC(x=2;y=1,3)

[0109] Under an argon atmosphere, polymer PS x IM y -OH (5 g) was dissolved in 300 mL of THF in a round-bottom flask. After dissolution, the flask was placed in an ice-water bath, and DMAP (2.53 g, 0.069 M) was added with stirring. Then, diketene (1.67 mL, 0.069 M) was slowly added dropwise. After the addition was complete, the reaction was carried out at 0 °C for 1 h, and then at room temperature for 4 h. Most of the solvent was removed by vacuum distillation, and then the product was precipitated in a large amount of ethanol. The crude product was washed three times with ethanol and dried under vacuum at 40 °C for three days until constant weight was obtained. The resulting pale yellow polymer was named PS. x IM y -AC, where AC represents the acetoacetyl group. The 1H NMR spectrum is attached. Figure 15 , 16 As shown.

[0110] 4) PS x IM y Preparation of -VU(x=2; y=1,3)

[0111] Taking PS2IM2-AC as an example, PS2IM2-AC (5 g, 0.99 mmol acetoacetyl) was dissolved in anhydrous toluene, and then 4,7,10-trioxo-1,13-tetanediamine (217 μL, 0.99 mmol) and p-toluenesulfonic acid (34.1 mg, 1.98 mmol, 50 mg / mL in THF) were added. The mixture was stirred at room temperature for 30 min, poured into glass petri dishes, and placed in a vacuum oven at 40 °C for 2 days, followed by 1 day at 80 °C. The resulting pale yellow film was named PS2IM2-VU, where VU represents vinyl carbamate. Other proportions of PS x IM y The preparation method of -VU is as described above.

[0112] Results and Discussion

[0113] 1) PS x IM y Synthesis and structural characterization of -VU(x=0,1,2,3;y=2)

[0114] The 1H NMR spectrum shows that the absorption peaks at δ = 7.20-6.85 are attributed to the meta- and para-hydrogens in block styrene and the protons in atactic styrene, with peak areas denoted as A1; the absorption peaks at δ = 6.32-6.85 correspond to the chemical shifts of the ortho-hydrogens in block styrene, with peak areas denoted as A2; the absorption peak at δ = 1.2 corresponds to the hydrogen on the ortho-carbon of the hydroxyl group in myrcene, with peak areas denoted as A3; and the absorption peaks at δ = 5.12 correspond to the absorption peaks of hydrogen on the unsaturated double bonds of isoprene and hydroxymyrcene, with peak areas denoted as A4. Since A1 / A2 = 3 / 2, the polystyrene segment is a pure block structure, and there are no atactic segments of polystyrene and polyisoprene. However, the DSC curve of the copolymer shows only one diene glass transition, indicating that the hydroxymyrcene and isoprene segments are atactic polymers, with a small amount of hydroxymyrcene monomer randomly distributed in the middle of the isoprene segments. The molar ratio of styrene, hydroxymyrcene (HMY), and isoprene units in the polymer can be calculated using Equation 1:

[0115]

[0116] Calculations show that as the styrene feed ratio increases, the styrene content in the polymerization product increases sequentially, while the hydroxymyrcene content remains basically unchanged.

[0117] Subsequently, the polymer PS x IM y The hydroxyl groups of the myrcene linkage in the -OH group were modified to obtain the acetylacetyl-functionalized polymer PS. x IM y-AC (AC represents the acetoacetyl group). See attached... Figure 4 -Appendix Figure 11 As shown, the absorption peak of hydroxymyrcene at δ = 1.2 disappears, and an absorption peak appears at δ = 3.34, corresponding to the hydrogen on the middle carbon of the two carbonyl groups in acetylated myrcene (HMY-AC). The peak area is denoted as A5. Polymer PS x IM y The molar ratio of styrene, acetylated myrcene, and isoprene units in AC can be calculated using Equation 2:

[0118]

[0119] Calculations showed that the molar ratios of each unit in different samples were similar to those before acetylation. Furthermore, the disappearance of the characteristic peak of hydroxyl myrcene indicated that all hydroxyl groups had undergone acetylation. (Polymer PS) x IM y The mass fractions of styrene units (PS) and acetylated myrcene units (PM) in AC can be calculated using equations 3 and 4:

[0120]

[0121]

[0122] As shown in Table 1, PS3IM2-AC had the highest styrene unit content (12.17 wt%), followed by PS2IM2-AC (9.77 wt%), and PS1IM2-AC had the lowest (6.20 wt%). The acetylated myrcene unit content in both the experimental and control groups was approximately 4.70 wt%, ensuring a consistent chemical crosslinking ratio. Gel permeation chromatography (GPC) analysis showed that the molecular weight and molecular weight distribution were essentially consistent, eliminating the influence of variables. According to the mass fraction ratio, a 1:1 molar equivalent (relative to acetoacetyl group content) of diamine crosslinking agent and a 0.5:1 molar equivalent (relative to acetoacetyl group content) of p-toluenesulfonic acid (Brønsted acid catalyst) were added to the polymer solution dissolved in toluene to obtain the crosslinked sample PS. x IM2-VU (x = 0, 1, 2, 3, VU represents the cross-linked vinyl urethane structure). Furthermore, toluene equilibrium swelling experiments demonstrated that the cross-linking density, gel fraction, and swelling ratio of the samples remained essentially constant with increasing styrene content, proving the consistency of the chemical cross-linking ratio. Figure 17 As shown. The equilibrium swelling experiment shows that, compared to PS... x IM y -AC differs, and the cross-linked PS x IM y-VU exhibits solvent resistance, swelling but not dissolving in toluene, a good solvent for raw rubber, demonstrating the formation of a cross-linked network.

[0123] Table 1: PS x Molecular weight, molecular weight distribution, mass fraction of each structural unit, cis content, and PS of IM2-AC x Crosslinking density of IM2-VU (x=0,1,2,3)

[0124]

[0125]

[0126] The polymer structure was analyzed using Fourier Transform Infrared Spectroscopy (FTIR). Figure 18 As shown, PS x The infrared spectrum of IM2-AC shows a position at 1745 cm⁻¹ -1 and 1718cm -1 The peak belongs to the stretching vibration absorption peak of the two carbonyl groups of the acetyl group. After crosslinking, PS x 1745 cm⁻¹ in the infrared spectrum of IM2-VU -1 and 1718cm -1 The peak has basically disappeared, and a new peak appears at 1652cm. -1 and 1609cm -1 The peaks correspond to the carbon-carbon double bond peak and carbonyl peak of vinyl urethane, respectively. This demonstrates the successful grafting and complete crosslinking of the acetoacetyl group, and the final crosslinked polymer contains no free acetoacetyl groups.

[0127] In summary, three PS samples with the same chemical crosslinking density but different styrene contents were successfully synthesized. x IM2-VU (x=1,2,3) and the styrene-free control polymer PSOIM2-VU ensured that styrene content was the biggest factor affecting the performance of different samples.

[0128] 2) PS x IM y Synthesis and structural characterization of -VU(x=2;y=1,2,3)

[0129] Based on the results of Example 1, the crosslinked elastomer exhibited the best overall performance when the styrene content was 9.77 wt% (x = 2). To investigate the effect of different crosslinking ratios on the elastomer's properties, we maintained a styrene content of 9.77 wt% and synthesized polymers PS with different crosslinking contents (i.e., hydroxymyrcene content). x IM y-OH (x=2,y=1,2,3) was added to modify the hydroxyl groups of the polymer to obtain the acetylacetyl-functionalized polymer PS. x IM y -AC. The calculation of the mass fractions of styrene and myrcene linkages, as well as the calculation of the cis content of the polymer, are as described above, and specific information is shown in Table 2. The myrcene contents are 2.59 wt%, 4.73 wt%, and 6.80 wt%, respectively, while the styrene content remains essentially unchanged, and the cis content is above 96% in all cases. Subsequently, diamine small molecules and p-toluenesulfonic acid are added at the same molar equivalent ratio as in Chapter 2 for crosslinking to obtain PS2IM. y -VU(y=1,2,3). Further, the crosslinking density, gel fraction, and swelling ratio of the samples were determined using an equilibrium swelling experiment, as detailed in [link to details]. Figure 19 As the myrcene content increases, the gel fraction increases, the swelling ratio decreases, and the crosslinking density increases, indicating the formation of a denser chemical crosslinking network. Furthermore, even PS2IM1-VU, with the lowest crosslinking density, only swells in toluene without dissolving, demonstrating that the material possesses a complete network structure and good solvent resistance.

[0130] Table 2: PS2IM y -AC molecular weight, molecular weight distribution, mass fraction of each structural unit, cis-structure content, and PS x Crosslinking density of IM2-VU (y = 1, 2, 3)

[0131]

[0132] The polymer structure was analyzed using Fourier transform infrared spectroscopy. Figure 20 As shown, PS2IM y -AC appears in the infrared spectrum at 1745 cm⁻¹ -1 and 1718cm -1 The peak value belongs to the stretching vibration absorption peak of the two carbonyl groups in the acetoacetyl group structure. PS2IM y In the infrared spectrum of -VU, the absorption peak of the acetoacetyl group almost completely disappears, and a peak appears at 1652 cm⁻¹. -1 and 1609cm -1 The peak values ​​belong to the carbon-carbon double bond peak and carbonyl peak of vinyl polyurethane, respectively. This demonstrates the successful grafting and complete crosslinking of the acetoacetyl group, and the final crosslinked polymer contains no free acetoacetyl groups.

[0133] Furthermore, the vinyl urethane bonds in the crosslinked rubber can form hydrogen bonds similar to those in polyurethane, with the proton donor being the -NH group and the proton acceptor being either a C=O group or a COC group. Therefore, there are two hydrogen bonding modes, as shown below:

[0134] I:>NH…O=C<

[0135] II:>NH…O<

[0136] In the infrared spectrum, the stretching vibration peak of the NH group is located at 3200–3600 cm⁻¹. -1 .like Figure 21 As shown, hydrogen bonding causes this stretching vibration region to split into two peaks. At 3280 cm⁻¹ -1 The weak absorption peaks around 3396 cm⁻¹ correspond to the stretching vibrations of hydrogen-bonded NH groups. -1 The strong absorption peaks on the left and right correspond to the stretching vibrations of non-hydrogen-bonded NH groups. It can be seen that as the myrcene content, i.e., the crosslinking ratio, increases, the intensity of the stretching vibration peak of the hydrogen-bonded NH groups increases, indicating that the number of hydrogen bonds increases to some extent with the increase of the crosslinking ratio. In summary, three PS2IM samples with the same styrene content but different crosslinking ratios were successfully prepared. y (y=1,2,3), ensuring that the crosslinking ratio is the biggest factor affecting the performance of different samples.

[0137] 3) Other performance

[0138] The stress-strain curves of the samples prepared in Examples 1 and 2 are as follows: Figure 22 As shown. The strength, Young's modulus, and toughness of the samples can be controlled by adjusting the content of the polystyrene phase and the crosslinking density. The strength and toughness of the samples were significantly improved upon the addition of polystyrene. When the polystyrene content was 9.77 wt%, PS2IM2 exhibited the highest strength and toughness, reaching 15.7 MPa and 41.0 MJ / m², respectively. 3 However, as the polystyrene content further increases, the sample strength decreases due to the reduced elongation at break. Furthermore, with increasing crosslinking density, the sample strength and toughness first increase and then decrease, similar to the effect of polystyrene on relative mechanical properties.

[0139] This invention further examines the elasticity of the samples through tensile recovery testing. The loading speed was 100 mm / min, the strain was set to 1, and the samples were held under tensile conditions of strain 1 for 10 minutes, followed by free relaxation under stress-free conditions. The instantaneous length of the samples after tensile recovery and the change in sample length after 15 minutes were recorded, and the permanent tensile deformation of the samples was calculated, as shown in Table 3. The degree of instantaneous deformation after stretching is directly proportional to the styrene content, but after 15 minutes, all samples could completely recover their initial length, and the permanent tensile deformation was 0. The degree of instantaneous deformation after stretching is inversely proportional to the crosslinking density; after 15 minutes, PS2IM1, with the lowest crosslinking density, still exhibited some permanent deformation. This indicates that the presence of 4.7 wt% chemical crosslinking phase can effectively improve the interfacial interaction between the PI and PS phases, making the PS phase in the sample more elastic.0-3 IM2 exhibits excellent elasticity. However, when the content of the chemically crosslinked phase decreases to 2.59 wt%, the elasticity of sample PS2IM1 decreases.

[0140] Table 3

[0141]

[0142] This invention further investigated the creep resistance of the samples through creep-recovery testing. For example... Figure 23 As shown, the introduction and increase of styrene content reduced creep and permanent deformation at 30℃ and 60℃. Furthermore, with increasing crosslinking density, creep and permanent deformation decreased at all temperatures. This indicates that increasing the polystyrene phase and crosslinking density can significantly enhance the dimensional stability of the network at the operating temperature, thus providing it with creep resistance.

[0143] This invention further investigated the relaxation properties of the specimens through stress relaxation testing. For example... Figure 24 As shown, the activation energy of the sample was obtained by fitting the expansion index and Arrhenius equation. It can be seen that the activation energy of the sample decreases after the introduction of the polystyrene phase, indicating that the polystyrene phase can promote dynamic bond exchange. Furthermore, increasing the crosslinking density also reduces the activation energy of the sample, indicating that the side-group effect generated by hydrogen bonding due to the crosslinking density can also promote dynamic bond exchange.

[0144] This invention further investigated the recovery performance of the samples by testing their stress-strain curves. After pulverizing, the samples were subjected to hot-pressing recovery at 150℃ and 10MPa for 30 minutes. Figure 25 The figure shows the mechanical property recovery efficiency of different samples. It can be seen that the introduction of the polystyrene phase significantly improves the sample recovery efficiency. (The figure also shows that the polystyrene phase-containing sample PS...) 1- The strength recovery efficiency of 3IM2 reached over 65%, and the toughness recovery efficiency reached over 70%. Furthermore, with the further increase in crosslinking density, the recovery efficiency of sample PS2IM3 even reached 100%.

[0145] This invention further compares the strength and elongation at break recycling performance of the PS2IM2 sample, which exhibits the best overall performance, with other dynamically covalently cross-linked diene elastomers (such as butadiene rubber PB, styrene-butadiene rubber SBR, natural rubber NR, isoprene rubber IR, etc.). Figure 26 As shown, PS2IM2 exhibits superior mechanical properties after reprocessing.

[0146] This invention further tested the self-healing performance of the samples through scratch repair experiments. For example... Figure 27As shown, the representative sample PS2IM2, after being scratched, was heated at 150℃. The scratches gradually became thinner over time, and after 1 hour, the scratches almost completely disappeared. This indicates that the sample has excellent self-healing properties.

[0147] In summary, this invention constructs a polystyrene-based dynamically covalently crosslinked polyisoprene elastomer with excellent overall properties by combining a polystyrene microphase separation structure with a polyisoprene dynamic covalent network. The resulting PS... x IM y -VU possesses tunable mechanical properties, excellent elasticity, creep resistance, relaxation, and self-healing capabilities. Samples can also be recovered through pulverization followed by hot pressing, yielding recovered samples with excellent recovery efficiency. The strength and elongation at break after a single recovery are significantly superior to other dynamically covalently crosslinked diene elastomers. This provides a new approach for preparing high-strength, creep-resistant, and recyclable diene elastomers.

[0148] Example 3

[0149] Polymer derivatives PS 1 x IM y Preparation of (S) 1 (Representing styrene monomer derivatives):

[0150] PS 1 x IM y -OH, PS 1 x IM y -AC、PS 1 x IM y -VU is prepared as in Example 1, wherein the styrene monomer can be replaced with a styrene derivative with a price advantage, such as 4-methylstyrene, 4-tert-butylstyrene, or 4-chlorostyrene.

[0151] Results and Discussion

[0152] This invention uses x=2, y=2, S 1 Taking 4-methylstyrene as an example, differential scanning calorimetry (DSC) was used to analyze the polymer PS. x IM y -OH and polymer derivatives PS 1 x IM y The phase structure of -OH was tested and analyzed. For example... Figure 28 As shown, both have two Ts g These correspond to the diene segment and the polystyrene segment, respectively, indicating that both have good phase separation structures, but PS 1 x IMy -OH corresponds to the T in the poly(4-methylstyrene) segment. g,PS 1 It is 102.3℃, higher than PS x IM y The glass transition temperature of -OH is 98.4℃. This also indicates that replacing styrene with styrene derivatives can adjust the glass transition temperature of the product, thereby improving the heat resistance of the material.

[0153] It should be noted that while the preferred embodiments of the present invention are given in the specification and accompanying drawings, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. These embodiments are not intended to impose additional limitations on the content of the present invention; their purpose is to provide a more thorough and comprehensive understanding of the disclosure of the present invention. Furthermore, the above-described technical features can be combined with each other to form various embodiments not listed above, all of which are considered to be within the scope of the present invention specification. Moreover, those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A high-strength, creep-resistant, recyclable diene elastomer, characterized in that, It has the following structure: ; Where a, b, m, and n are each integers greater than 1, and R is selected from hydrogen, halogen, or alkyl.

2. The high-strength, creep-resistant, recyclable diene elastomer according to claim 1, characterized in that, It is prepared by the following method: first, a block polymer of styrene or its derivatives with isoprene and hydroxymyrcene is obtained, and then the obtained block polymer is subjected to acetylation and cross-linking treatment in sequence to obtain a diene elastomer with vinyl urethane bond cross-linking.

3. The high-strength, creep-resistant, recyclable diene elastomer according to claim 1 or 2, characterized in that, The mass fraction of styrene segments in the high-strength, creep-resistant, recyclable diene elastomer is 5-13%.

4. The high-strength, creep-resistant, recyclable diene elastomer according to claim 2, characterized in that, The mass fraction of hydroxymyrcene units in the high-strength, creep-resistant, recyclable diene elastomer is 2-7%.

5. The high-strength, creep-resistant, recyclable diene elastomer according to claim 1 or 2, characterized in that, The crosslinking ratio of the high-strength, creep-resistant, recyclable diene elastomer is 3×10. -5 mol / cm 3 -14×10 -5 mol / cm 3 .

6. The high-strength, creep-resistant, recyclable diene elastomer according to claim 2, characterized in that, The high-strength, creep-resistant, recyclable diene elastomer contains over 96% cis-isoprene and hydroxymyrcene copolymer segments.

7. A method for preparing high-strength, creep-resistant, recyclable diene elastomers, characterized in that, It includes the following steps: First, a block polymer of styrene or its derivatives with isoprene and hydroxymyrcene is prepared. Then, the obtained block polymer is subjected to acetylation and crosslinking treatments in sequence to obtain a diene elastomer with vinyl urethane bond crosslinking.

8. The method according to claim 7, characterized in that, Includes the following steps: (1) Preparation of block polymers of styrene or its derivatives with isoprene and hydroxymyrcene: styrene or its derivative monomers dissolved in organic solvent I are polymerized for a period of time in the presence of catalyst I. Then, a mixed solution of hydroxymyrcene aluminum oxychloride monomer and isoprene monomer is added for copolymerization. The reaction is then quenched. The resulting products are washed with acidified water and alcohol solvents, and dried to obtain the block polymer. (2) Preparation of acetylated styrene or its derivatives into block polymers with isoprene and hydroxymyrcene: Under a protective atmosphere, the block polymer obtained in step (1) is dissolved in organic solvent II, and then acylated with diketene in the presence of catalyst II. The organic solvent II is removed by vacuum distillation. The resulting product is precipitated with solvent, washed and dried to obtain the acetylated block polymer. (3) Preparation of a block polymer of styrene or its derivatives crosslinked with vinyl urethane bonds and isoprene and hydroxymyrcene: The acetylated block polymer obtained in step (2) is dissolved in organic solvent III, and then a diamine crosslinking agent and catalyst III are added to carry out a crosslinking reaction to obtain a block polymer of styrene or its derivatives crosslinked with vinyl urethane bonds and isoprene and hydroxymyrcene, which is the high-strength creep-resistant recyclable diene elastomer.

9. The method according to claim 8, characterized in that, The hydroxymyrcene aluminum oxychloride monomer is prepared as follows: the independent double bonds of myrcene are epoxidized with m-chloroperoxybenzoic acid to obtain epoxidized myrcene; lithium aluminum hydride is used to perform an epoxidation-reduction reaction with epoxidized myrcene to obtain hydroxymyrcene; and alkyl aluminum is used to perform a hydroxy dehydrogenation reaction with hydroxymyrcene to obtain the hydroxymyrcene aluminum oxychloride monomer.

10. The method according to claim 9, characterized in that, The alkylaluminum is diisobutylaluminum hydride.

11. The method according to claim 8, characterized in that, Catalyst I is a mixture of substances A, B, C, and D, wherein the molar ratio of substances A, B, C, and D is: A:B:C:D = 0.8-1.2:10-20:15-25:0.08-0.12; Substance A is neodymium carboxylic acid, neodymium alcohol, neodymium phosphate, neodymium acetylacetone, or neodymium amino acid; Substance B is triisobutylaluminum, trimethylaluminum, triethylaluminum, or diisobutylaluminum hydride; Substance C is chloroform, diisobutylaluminum chloride, dichlorodimethylsilane, tert-butyl chloride, tetrachloromethane, diethylaluminum chloride, aluminum trichloride, diethylaluminum chloride, or trichlorotriethylaluminum; Substance D is ethyl trichloroacetate, butyl trichloroacetate, isoamyl trichloroacetate, or ethyl trichlorobutyrate.

12. The method according to claim 11, characterized in that, A:B:C:D = 1:15:20:0.

1.

13. The method according to claim 11, characterized in that, Substance A is neodymium neodecanoate; Substance B is triisobutylaluminum; Substance C is chloroform; Substance D is ethyl trichloroacetate.

14. The method according to claim 11, characterized in that, The block polymers of styrene or its derivatives prepared using catalyst I, with isoprene and hydroxymyrcene, have a cis content of isoprene and hydroxymyrcene copolymer segments of over 96%.

15. The method according to claim 11, characterized in that, In step (1), the first part of styrene or its derivative monomers is aged with substances A and B in catalyst I at 40-60°C for 5-20 min, then substances C and D are added, and the reaction continues for 0.5-2 h. Then the second part of styrene or its derivative monomers is added, and polymerization is carried out at 40-60°C for 5-20 h, wherein the molar ratio of the first part of styrene or its derivative monomers to the second part is 1:20-50.

16. The method according to claim 15, characterized in that, In step (1), the molar ratio of styrene or its derivative monomer to substance A in catalyst I is 420-1020:0.8-1.

2.

17. The method according to claim 16, characterized in that, In step (1), the molar ratio of styrene or its derivative monomer to substance A in catalyst I is 820:

1.

18. The method according to claim 8, characterized in that, In step (1), the molar ratio of styrene or its derivative monomer, isoprene monomer and hydroxymyrcene aluminosilicate monomer is 163.8-397.8:410-468:5.85-20.

5.

19. The method according to claim 8, characterized in that, In step (1), the molar ratio of styrene or its derivative monomer, isoprene monomer and hydroxymyrcene aluminosilicate monomer is 319.8:429:12.

8.

20. The method according to claim 8, characterized in that, The organic solvent I in step (1) is cyclohexane, n-hexane, or n-heptane.

21. The method according to claim 8, characterized in that, In step (1), the copolymerization is carried out at 40-60°C for 5-20 hours.

22. The method according to claim 8, characterized in that, In step (1), the quenching reaction is carried out using ethanol.

23. The method according to claim 8, characterized in that, In step (2), the protective atmosphere is a nitrogen or argon protective atmosphere.

24. The method according to claim 8, characterized in that, In step (2), the organic solvent II is tetrahydrofuran or toluene.

25. The method according to claim 8, characterized in that, In step (2), the catalyst II is 4-dimethylaminopyridine.

26. The method according to claim 8, characterized in that, In step (2), catalyst II is added to the block polymer solution under ice bath and stirring conditions, followed by the addition of divinyl ketone.

27. The method according to claim 8, characterized in that, In step (2), the acylation reaction is carried out at 0°C for 0.5-1.5 h, and then at room temperature for 3-5 h.

28. The method according to claim 8, characterized in that, In step (2), the resulting product is precipitated in ethanol and washed with ethanol.

29. The method according to claim 8, characterized in that, In step (3), the organic solvent III is anhydrous toluene or anhydrous tetrahydrofuran.

30. The method according to claim 8, characterized in that, In step (3), the diamine crosslinking agent is 4,7,10-trioxo-1,13-tetanediamine.

31. The method according to claim 8, characterized in that, In step (3), catalyst III is p-toluenesulfonic acid.

32. The method according to claim 8, characterized in that, In step (3), a diamine crosslinker with a content of 1:1 molar equivalent relative to the acetylated styrene or its derivative in the block polymer of isoprene and hydroxymyrcene and a catalyst III with a content of 0.5:1 molar equivalent are added.

33. The method according to claim 7, characterized in that, The high-strength, creep-resistant, recyclable diene elastomer prepared by the method has a styrene unit mass fraction of 5-13%.

34. The method according to claim 7, characterized in that, The high-strength, creep-resistant, recyclable diene elastomer prepared by the method has a hydroxymyrcene unit mass fraction of 2-7%.

35. The method according to claim 7, characterized in that, The crosslinking ratio of the high-strength, creep-resistant, recyclable diene elastomer prepared by the method is 3 × 10⁻⁶. -5 mol / cm 3 -14×10 -5 mol / cm 3 .

Citation Information

Patent Citations

  • Rare earth catalyst, preparation method and applications thereof

    CN110903423A